Sub-lethal doses of albendazole induce drug metabolizing enzymes and increase albendazole deactivation in Haemonchus contortus adults - Kellerová, Pavlína; Raisová Stuchlíková, Lucie; Matoušková, Petra; Štěrbová, Karolína; Lamka, Jiří; Navrátilová, Martina; Vokřál, Ivan; Szotáková, Barbora; Skálová, Lenka (Veterinary research, 2020)
The efficacy of anthelmintic therapy of farm animals rapidly decreases due to drug resistance development in helminths. In resistant isolates, the increased expression and activity of drug-metabolizing enzymes (DMEs), e.g. cytochromes P450 (CYPs), UDP-glycosyltransferases (UGTs) and P-glycoprotein transporters (P-gps), in comparison to sensitive isolates have been described. However, the mechanisms and circumstances of DMEs induction are not well known. Therefore, the present study was designed to find the changes in expression of CYPs, UGTs and P-gps in adult parasitic nematodes Haemonchus contortus exposed to sub-lethal doses of the benzimidazole anthelmintic drug albendazole (ABZ) and its active metabolite ABZ-sulfoxide (ABZSO). In addition, the effect of ABZ at sub-lethal doses on the ability to deactivate ABZ during consequent treatment was studied. The results showed that contact of H. contortus adults with sub-lethal doses of ABZ and ABZSO led to a significant induction of several DMEs, particularly cyp-2, cyp-3, cyp-6, cyp-7, cyp-8, UGT10B1, UGT24C1, UGT26A2, UGT365A1, UGT366C1, UGT368B2, UGT367A1, UGT371A1, UGT372A1 and pgp-3, pgp-9.1, pgp-9.2, pgp-10. This induction led to increased formation of ABZ metabolites (especially glycosides) and their increased export from the helminths' body into the medium. The present study demonstrates for the first time that contact of H. contortus with sub-lethal doses of ABZ (e.g. during underdose treatment) improves the ability of H. contortus adults to deactivate ABZ in consequent therapy.
Keywords: antinematodní látky; Haemonchus; Animals; léková rezistence; vztah mezi dávkou a účinkem léčiva; Drug Resistance; zvířata; Dose-Response Relationship, Drug; Inactivation, Metabolic; Antinematodal Agents; albendazol; Albendazole; metabolická inaktivace